The IMPLEMENTATION OF A SMOKE-FREE AREA POLICY IN SMA NEGERI 2 NGANJUK - Yeny Kusumawati; Fresty Africia (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2020)
Background:Smoke-free policies in school established to protect and reduce young students' smoking rates from cigarette smoke's harmfulness. This research to describe implementation of smoke-free policies in school and determine factors influencing the policy's implementation. Method: Qualitative research design and descriptive. Informants determined use purposive sampling. Subjects research were headmaster, student vice headmaster, counseling teachers, homeroom teachers, employees, and students. Technique data collection were observation, interviews, and documentation. Validity data was checked with triangulation technique. Qualitative data analysis used an interactive model based on theory of George C. Edward III, which consists of communication, resources, dispositions, and bureaucratic structures. Result: Smoke-free policies in school hasn’t been implemented optimally, especially in the resource. There are some teachers and employees who still smoke. There isn’t specific budget for the implementation of the smoke-free policies. Billboards facilities with no smoking or smoke-free area are still limited. Supporting factor is communication; smoke-free area policy always communicated to school residents. Disposition factor; there is commitment of policy implementers. Bureaucratic structure factor; there is SOP's existence in implementing the policies. Conclusion: Implementation of smoke-free policies in school has not been maximized, so it needs to be supported by all factors, both communication factors, resource factors, disposition factors, and bureaucratic factors. Keywords: implementation, policy, smoke-free area